Compassion: From Its Evolution to a Psychotherapy - Gilbert, Paul (Frontiers in Psychology, 2020)
The concept, benefits and recommendations for the cultivation of compassion have been recognised in the contemplative traditions for thousands of years. In the last 30 years or so, the study of compassion has revealed it to have major physiological and psychological effects influencing wellbeing, addressing mental health difficulties and promoting prosocial behaviour. This paper outlines an evolution informed biopsychosocial, multicomponent model to caring behaviour and its derivative ‘compassion’ that underpins newer approaches to psychotherapy. The paper explores the origins of caring motives and the nature and functions of caring-attachment behaviour. These include providing a secure base (sources of validation, encouragement and guidance) and safe haven (source of soothing and warmth) for offspring and can be central for compassion focused therapy. Second, it suggests that it is the way recent human cognitive competencies give rise to different types of ‘mind awareness’ and ‘knowing intentionality’ that transform basic caring motives into potentials for compassion. While we can care for our gardens and treasured objects, the concept of compassion is only used for sentient beings who can ‘suffer’. As psychotherapy addresses mental suffering, cultivating the motives and competencies of compassion to self and others can be a central focus for psychotherapy.